Analisis Proses Pembuatan Batik Guna Membentuk Karakter Dan Moral Budaya Para Karyawan Atau Pengrajin Di Sanggar Batik Liza Mangrove Desa Pematang Johar Deli Serdang - Athariq, Difa; Permatasari, Dilla; Ardiansyah, Dimas; Suciyati, Putri; Zainarti (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
The purpose of this research is to determine whether the batik making process at the Liza Mangrove Batik Studio can shape the character and cultural morals of employees or craftsmen. The method applied in this research is a qualitative descriptive approach. The data collection techniques used in this research were interviews and documentation. The results of the research show that the process of making Batik at the Liza Mangrove Batik Studio in Pematang Johar Village has 6 stages, namely, making motifs, tracing the fabric, casting, filling in the motif (isen), adding color and ngelorod. Batik is not only an art product, but also a valuable character education tool. Batik making is not only a technical process, but also a vehicle for learning traditional values ​​and work ethics that are important for craftsmen. This process teaches about patience, creativity, respect for cultural heritage, cooperation, and high work morals